2014
DOI: 10.1186/1756-0500-7-349
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Trachomatis and Neisseria Gonorrhoeae prevalence among women of reproductive age living in urogenital schistosomiasis endemic area in Ghana

Abstract: BackgroundMany studies have shown an overlap in the epidemiology of sexually transmitted infections (STIs) and urogenital schistosomiasis among young women living in schistosomiasis endemic areas. Yet we found no study assessing the prevalence of STI infections in urogenital schistosomiasis endemic areas in Ghana. As part of an epidemiological study on urogenital schistosomiasis and HIV, we sought to assess the prevalence of both Chlamydia trachomatis (CT) and Neisseria gonorhoeae (NG) infections among women l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
(21 reference statements)
5
25
0
Order By: Relevance
“…According to findings of this study bacterial infection has higher rate among women with use of withdrawal method. These results are similar to the results reported by Yirenya-Tawiah et al and Akya et al (23, 46). As shown in the results of this study, only 7% of women have used barrier methods, it seems that the high prevalence of chlamydia and gonorrhea among women in this study partly can be explained through it.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to findings of this study bacterial infection has higher rate among women with use of withdrawal method. These results are similar to the results reported by Yirenya-Tawiah et al and Akya et al (23, 46). As shown in the results of this study, only 7% of women have used barrier methods, it seems that the high prevalence of chlamydia and gonorrhea among women in this study partly can be explained through it.…”
Section: Discussionsupporting
confidence: 93%
“…These results was concordance with the study performed by Yirenya-Tawiah et al in Ghana, Nevertheless, they observed only a small percentage of the STI positive cases to report the presence of symptoms related to STIs (46). In a study was done in Batswana, many Chlamydia trachomatis and Neisseria gonorrhoeae infected individuals were asymptomatic (47).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, higher infection rates were shown in the 15–24 age group elsewhere [12, 21]. Therefore, the prevalence of CT in adolescent females in this country is an important health concern since untreated CT infection may be a reservoir for ongoing transmission in the population and could have long-term consequences, which may not manifest themselves until women later try to conceive.…”
Section: Discussionmentioning
confidence: 88%
“…The total study population size screened for Chlamydia trachomatis and involved in this systematic review and meta-analysis were 17,119.Among these, 9606 were screened at community based studies [ 18 23 ], about 2638 were FCSWS [ 19 , 20 , 24 – 28 ] and 4875 were at health facility based studies [ 28 – 38 ]. The sample size of study population varied from 100 [ 24 ] to 4886 [ 19 ], and were conducted between the year 1997–2001 [ 19 , 22 , 30 ], 2002–2006 [ 25 ], 2007–2011 [ 21 , 26 , 31 ] and 2012–2016 [ 23 , 27 , 34 – 36 ].…”
Section: Resultsmentioning
confidence: 99%